The influence of knowledge about environmental change, information reception, and naturalistic intelligence on environmental care - Nurfiana Abdullah; Firdaus Daud; Muhammad Darwis; Muhiddin Muhiddin; Arifah Novia Arifin (Universitas Negeri Jakarta, 2023)
This study is an ex post facto research that aims to discover the influence of knowledge on environmental changes, receiving information, on environmental awareness and the influence of environmental changes, receiving information on environmental awareness by involving naturalistic intelligence. The study population was all students of grade XI at SMAN in East Banggae subdistrict in Majene district, namely SMAN 1 Majene, SMAN 2 Majene, and SMAN 3 Majene. The research instrument employed a test of environmental change knowledge, a questionnaire for information reception, naturalistic intelligence and environmental awareness. The results showed that, 1) environmental changes are in the very low category, information reception is in the medium category, naturalistic intelligence is in the high category.